(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Cardiovascular diseases (CVDs) are one of the leading causes of morbidity and mortality worldwide and represent a major public health challenge in India. Increasing prevalence of obesity, dyslipidemia, smoking, sedentary lifestyle, and other behavioural risk factors contribute significantly to the growing burden of CVDs. Methodology: A hospital-based cross-sectional study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from May 2025 to March 2026 among individuals attending routine medical check-ups. Demographic details, anthropometric measurements, blood pressure, lipid profile, smoking status, physical activity, and socioeconomic status were assessed using a structured proforma. Cardiovascular risk was evaluated using the Joint British Societies for the Prevention of Cardiovascular Disease (JBS3) risk assessment tool. Results: The study demonstrated a high prevalence of overweight and obesity, particularly among females. Hypertriglyceridemia and low HDL were more common in females, whereas elevated LDL and hypercholesterolemia were predominantly observed in males. Physical inactivity and smoking were highly prevalent among participants. Most individuals belonged to lower socioeconomic classes. Conclusion: The findings indicate a high burden of modifiable cardiovascular risk factors among apparently healthy individuals, emphasizing the importance of early screening, lifestyle modification, and preventive interventions.